Adjuvant radiation and cetuximab improves local control in head and neck cutaneous squamous cell carcinoma: Phase II study. Issue 11 (7th August 2021) - Kreinbrink, Paul J.; Mierzwa, Michelle L.; Huth, Brad; Redmond, Kevin P.; Wise‐Draper, Trisha M.; Casper, Keith; Li, Junan; Takiar, Vinita
Abstract: Background: Cutaneous squamous cell carcinoma of the head/neck (CSCCHN) is common due to chronic sun exposure. As CSCCHN highly expresses EGFR, we prospectively studied postoperative concurrent cetuximab with radiotherapy for locally advanced CSCCHN (LA‐CSCCHN). Materials and methods: Single‐institutional phase II trial of LA‐CSCCHN (NCT XXXX). Adjuvant radiation was given with concurrent cetuximab. Primary endpoint of 2‐year LRC and secondary objectives of 2‐year disease‐free survival (DFS) and 2‐year OS were assessed by Kaplan–Meier analysis. Results: Twenty‐four patients ages 47–88 (median 71 years) were treated from 2014 to 2017. Fourteen patients had T3/4 disease, 5 had N1 disease, and 7 were N2/3. At median follow‐up of 42 months, median OS and DFS was not reached and 64 months. Two‐year OS was 75%, 2‐year DFS was 70.8%. LRC was 91.1% at 2 years. All grade 3 adverse events were related to skin toxicity (12.5% radiation‐related dermatitis, 16.7% cetuximab‐related rash). Conclusions: LRC compares favorably to historical data examining postoperative radiation alone but requires further investigation.